CKS1 Germ Line Exclusion Is Essential for the Transition from Meiosis to Early Embryonic Development - Ellederova, Zdenka; Del Rincon, Sonia; Koncicka, Marketa; Susor, Andrej; Kubelka, Michal; Sun, Dahui; Spruck, Charles (Molecular and cellular biology, 2019)
Cell division cycle (Cdc) kinase subunit (CKS) proteins bind cyclin-dependent kinases (CDKs) and play important roles in cell division control and development, though their precise molecular functions are not fully understood. Mammals express two closely related paralogs called CKS1 and CKS2, but only CKS2 is expressed in the germ line, indicating that it is solely responsible for regulating CDK functions in meiosis. Using cks2-/- knockout mice, we show that CKS2 is a crucial regulator of maturation-promoting factor (MPF; CDK1-cyclin A/B) activity in meiosis. cks2-/- oocytes display reduced and delayed MPF activity during meiotic progression, leading to defects in germinal vesicle breakdown (GVBD), anaphase-promoting complex/cyclosome (APC/C) activation, and meiotic spindle assembly. cks2-/- germ cells express significantly reduced levels of the MPF components CDK1 and cyclins A1/B1. Additionally, injection of MPF plus CKS2, but not MPF alone, restored normal GVBD in cks2-/- oocytes, demonstrating that GVBD is driven by a CKS2-dependent function of MPF. Moreover, we generated cks2cks1/cks1 knock-in mice and found that CKS1 can compensate for CKS2 in meiosis in vivo, but homozygous embryos arrested development at the 2- to 5-cell stage. Collectively, our results show that CKS2 is a crucial regulator of MPF functions in meiosis and that its paralog, CKS1, must be excluded from the germ line for proper embryonic development.
Keywords: Male; Mice, Knockout; mezotelin; oocyty; developmental biology; Gene Knock-In Techniques; Maturation-Promoting Factor; Embryonic Development; Meiosis; mužské pohlaví; meiosis; faktor podporující zrání; myši knockoutované; cyclin-dependent kinases; proteiny buněčného cyklu; CKS; meióza; Animals; genový knockin; ženské pohlaví; zvířata; CDC2-CDC28 Kinases; embryonální vývoj; myši; kinasy CDC2-CDC28; Mice; Female; Mesothelin; Cell Cycle Proteins; Oocytes